Aplikasi Pengaturan Menu Makanan Diet Menggunakan Metode Genetic Algorithm berbasis Android - Nita Hidayat; Andreas Handojo; Anita Nathania Purbowo (Jurnal Infra, 2020)
A diet is a healthy lifestyle that helps people control their eating habits with losing weight as the main goal. As time goes on, diet has also been developed into various types and each type of diet even has specific goals for people certain allergies or diseases. However, often people are less able to apply a good and correct diet because they do not know what type of diet is suitable and how to set the right food menu.To help people go on a diet, an application is made that can adjust the diet food menu according to the person's condition based on the profile data entered into the application. The method used in creating the diet menu is Genetic Algorithm. This diet application was created and developed for smartphone. The results of the application will provide a food menu arrangement for a week in accordance with user profile data.The test results show that the factors that influence the length of time running the Genetic Algorithm process are the number of epochs and the number of population used. The greater the number of epochs or the amount of population used, the longer the running time duration of the Genetic Algorithm process.